The evaluation of serum leptin level and other hormonal parameters in children with severe malnutrition - Kilic, M; Taskin, E; Ustundag, B; Aygun, AD (Pergamon-Elsevier Science Ltd, 2004)
Objectives: Protein-energy malnutrition (PEM) is a clinical problem caused by inadequate intake of one or more nutritional elements, and remains as one of the most important health problems in developing countries. The aim of this study is to determine the relationship among leptin concentrations, body weight and concentrations of some serum hormones, e.g., basal GH, IGF-1, basal cortisol and IGF-BP3, in severe malnourished children, and to determine the effects of leptin in malnourished children. Design and methods: The study group consisted of 36 children diagnosed with PEM. Thirty healthy children were enrolled as the control group. After an overnight fast and before initiation of feedings, fasting venous blood samples were obtained from a forearm vein with needle technique for routine tests, and leptin, IGF-1, IGF-BP3, basal GH and cortisol levels were measured. Tests were carried out in the laboratories of the Department of Biochemistry by commercial kits. Results: Serum leptin levels of infants with marasmus and kwashiorkor were significantly lower than that of the controls (2.09 +/- 0.93 and 2.27 +/- 1.01, 6.82 +/- 2.28 ng/ml, respectively, P < 0.001). However, there was no significant difference between serum leptin levels in children with marasmus and those with kwashiorkor (P > 0.05). Serum IGF-1 and IGF-BP3 levels were significantly lower in malnourished children (P < 0.001, both). Also, basal GH and cortisol levels were significantly higher in malnourished children (P < 0.001, both). There was a positive correlation among serum leptin levels and IGF-1 and IGF-BP3 levels and also a negative correlation among serum leptin levels and basal GH and cortisol levels in children diagnosed with marasmus or kwashiorkor and the control group. Conclusions: The decrease of energy intake and adipose tissue and serum IGF-1 levels in children with PEM may result in decrease of leptin secretion. Decrease in serum leptin levels may initiate food intake by increasing appetite and stimulating the secretion of cortisol and GH that might increase energy expenditure through an autocrine mechanism. Moreover, serum leptin level may be an important signal to reflect the metabolism of children with PEM. (C) 2004 The Canadian Society of Clinical Chemists. All rights reserved.
Keywords: malnutrition; leptin; IGF-1; growth hormone; cortisol